2014
DOI: 10.3892/mmr.2014.2829
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the human cytomegalovirus-encoded UL142 and cellular Snapin proteins

Abstract: Abstract. Human cytomegalovirus (HCMV) infectioncan cause severe illness in immunocompromised and immunodeficient individuals. As a novel HCMV-encoded major histocompatibility complex class I-related molecule, the UL142-encoded protein (pUL142) is capable of suppressing natural killer (NK) cell recognition in the course of infection. However, no host factors that directly interact with HCMV pUL142 have been reported so far. In order to understand the interactions between HCMV pUL142 and host proteins, the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Functionally, this reduced both CD8 + T and NK cell activation. The effect of UL148 was greatest on NK cell activation in the context of antibody dependent cellular cytotoxicity (ADCC), which is consistent with reports that the CD2:CD58 pathway contributes significantly to this process ( 54 ). Perhaps even more significantly for the host, ADCC was detected against Merlin-infected cells regardless of a full complement of NK evasion genes.…”
Section: Introductionsupporting
confidence: 89%
“…Functionally, this reduced both CD8 + T and NK cell activation. The effect of UL148 was greatest on NK cell activation in the context of antibody dependent cellular cytotoxicity (ADCC), which is consistent with reports that the CD2:CD58 pathway contributes significantly to this process ( 54 ). Perhaps even more significantly for the host, ADCC was detected against Merlin-infected cells regardless of a full complement of NK evasion genes.…”
Section: Introductionsupporting
confidence: 89%
“…Another study showed that snapin acts as a dynein motor adaptor and coordinates retrograde transport and late endosomal–lysosomal trafficking, thereby maintaining efficient autophagy–lysosomal function in neurons ( Cai and Sheng, 2011 ). It has been reported that the viral proteins pul130, ul70, ul105, and UL142 interact with the host protein snapin and affect viral DNA replication in human cytomegalovirus infection ( Shen et al, 2011 ; Luo et al, 2013 ; Liu et al, 2015 ; Wang et al, 2016 ). After infection in bees, DWV can cause abnormal neural activity and movement.…”
Section: Discussionmentioning
confidence: 99%
“…Interacts with Snapin [408]; Downregulates ULBP3, protects cells from NK cytotoxicity [409] Immune evasion [406,407,409]…”
Section: Ul145mentioning
confidence: 99%